Misinterpretation of the mouse ECG: 'musing the waves of Mus musculus'. (29th September 2014) - Boukens, Bastiaan J.; Rivaud, Mathilde R.; Rentschler, Stacey; Coronel, Ruben
Abstract The ECG is a primary diagnostic tool in patients suffering from heart disease, underscoring the importance of understanding factors contributing to normal and abnormal electrical patterns. Over the past few decades, transgenic mouse models have been increasingly used to study pathophysiological mechanisms of human heart diseases. In order to allow extrapolation of insights gained from murine models to the human condition, knowledge of the similarities and differences between the mouse and human ECG is of crucial importance. In this review, we briefly discuss the physiological mechanisms underlying differences between the baseline ECG of humans and mice, and provide a framework for understanding how these inherent differences are relevant to the interpretation of the mouse ECG during pathology and to the translation of the results from the mouse to man.